Simultaneous double side grinding of silicon wafers: a literature review - Li, Z. C.; Pei, Zhijian J.; Fisher, Graham R. (My University, 2006)
Silicon wafers are the most widely used substrates for fabricating integrated circuits (ICs). The quality of ICs depends directly on the quality of silicon wafers. A series of processes are required to manufacture high quality silicon wafers. Simultaneous double side grinding (SDSG) is one of the processes to flatten the wire-sawn wafers. This paper reviews the literature on SDSG of silicon wafers, covering the history, machine development (including machine configuration, drive and support systems, and control system), and process modeling (including grinding marks and wafer shape). It also discusses some possible topics for future research.
Keywords: Grinding; Machining; Modeling; Semiconductor material; Silicon wafer; Simultaneous double side grinding